Endangered ornamental plants are the effects of global climate change on the spread of the Liriodendron Chinense and Liriodendron tulipfera - Rasuljon Khaydaraliev; Rasuljon Khaydaraliev (Zien Journals, 2023)
Climate change has a significant impact on the number and distribution of species, biodiversity and ecological status. Liriodendron contains two species: Liriodendron chinense and Liriodendron tulipfera, both considered an ornamental tree and rich in unique nectar (honey), in addition, high-quality wood for furniture is important for medicinal and landscape purposes. However, little is known to us about the distribution characteristics of their population and the important climatic factors that shape their suitability. Global warming, climate change have become the most influential, decisive factor in the distribution of these two species in nature. Predicting the spatial variation and migration trend of species distributions endangered by climate change has become one of the latest research points in biology and forest ecology conservation. In order to develop strategies for future forest cultivation, management and conservation, the data obtained using prediction of distribution areas using the MaxEnt program of these two tree species will be the basis for further biogeographic research.
Keywords: Liriodendron chinense; liriodendron tulipfera; global warming